PREVENTION OF VIOLENCE AGAINST CHILDREN AT HOME IN COVID 19 PANDEMIC - Nursariani Simatupang (Proceeding International Seminar of Islamic Studies, 2021)
When covid 19 pandemic children follow the online learning from home. The child assigment is not only to write answers on paper, there are also make videos, and uploaded to youtube. Some children can't do it by them selves. The problem is that parent are upset when guiding a child to study at home. Parents often experience stress when dealing with the child's subject matter and tasks. This can lead to parental violence against the child. Child abuse has a negative impact. Therefore, it is necessary to prevent violence against children at home in covid 19 pandemic. The research is normative juridical research. The data sources in this research is secondary data.The technique to collecting data is documentation study.Based on the research discovered that violence against children negatively impacts who are lazy to learn and will not do school work and children are easily criminals of violence. Some prevention efforts to prevent children becoming victims of violence by parents are parents should understand that educating the child is main task, patiently accompanying and guiding the child, understanding the impact of violence to child, becoming a role model, building good communication, and always motivating themselves. Keywords: Prevention, Violence, Home.